2021
DOI: 10.3390/ijerph18052598
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Childhood Maltreatment on Non-Suicidal Self-Injury in Male Adolescents: The Moderating Roles of the Monoamine Oxidase A (MAOA) Gene and the Catechol-O-Methyltransferase (COMT) Gene

Abstract: (1) Background: Numerous studies suggest strong associations between childhood maltreatment and nonsuicidal self-injury (NSSI); this is also true for the roles of dopaminergic genes in the etiology of some psychopathologies related to NSSI. Investigating the interactions of environments and genes is important in order to better understand the etiology of NSSI. (2) Methods: Within a sample of 269 Chinese male adolescents (Mage = 14.72, SD = 0.92), childhood maltreatment and NSSI were evaluated, and saliva sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
2
9
0
Order By: Relevance
“…In this study, the MDD adolescents with self-injury behavior is mainly in the middle school stage, which is basically consistent with previous research results ( Swannell et al, 2014 ; Gao et al, 2021 ; Jiang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the MDD adolescents with self-injury behavior is mainly in the middle school stage, which is basically consistent with previous research results ( Swannell et al, 2014 ; Gao et al, 2021 ; Jiang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Regression analysis was used to explore whether baseline P300 can be used as a neural marker to predict the clinical efficacy of sertraline tablets in the treatment of adolescent MDD with NSSI behavior. In this study, the MDD adolescents with self-injury behavior is mainly in the middle school stage, which is basically consistent with previous research results (Swannell et al, 2014;Gao et al, 2021;Jiang et al, 2021). P300 incubation period is an electrophysiological index reflecting the speed of mental activities, and its amplitude can reflect the utilization of effective resources by the brain in information processing, which mainly depends on the sensitivity of the patient to stimulation (Duncan et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, a relationship between reports of an invalidating emotional environment during childhood and the development of NSSI was found only among Val carriers of the brain derived neurotrophic factor (BDNF; Val66Met polymorphism) compared to Met carriers (Hankin et al, 2015). In a population-based sample of Chinese adolescent males, Gao et al (2021) found a three-wave interaction between experiences of childhood abuse with variants of the MAOA and COMT genes in the prediction of NSSI: only in a subgroup of carriers with the T allele of the MAOA gene and the Met allele of COMT, there was no significant relation between experiences of abuse and the development of NSSI.…”
Section: Genesmentioning
confidence: 99%
“…Past research suggests these biases in reward processing systems may be present in SH [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a genetic predisposition to lower dopamine transmission is correlated with greater SH in individuals with bulimia 15 and in individuals who experienced child abuse 16 . Using fMRI, neural activity in reward-related regions has been shown to be both higher 18.19 and lower 17 when anticipating monetary rewards in SH groups compared with healthy controls, which may be associated with predisposition to SH like in other addictive behaviours 20 .…”
Section: Introductionmentioning
confidence: 99%